2015
DOI: 10.1155/2015/531296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacrificing Tensor Tympani Muscle Tendon When Manubrium of Malleus Is Foreshortened in Type I Tympanoplasty

Abstract: The current study aims at observing effects of sacrificing the tensor tympani tendon when manubrium of malleus is foreshortened or retracted on graft uptake, hearing improvement, and occurrence of complications if any during type I tympanoplasty surgery for central perforations. 42 patients were included in group A where the tensor tendon was sectioned and 42 patients were included in group B where the tensor tympani tendon was retained and kept intact. Graft uptake rates are very good in both groups but heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…After postoperative evaluation, it was concluded that, though the graft take-up rates in both of the groups were the same, the hearing improvements were found to be significantly better in the group where correction of foreshortening was done. No other study from the Indian author under mentioned criteria of search was found to have published on this topic [44].…”
Section: Techniques Of Surgerymentioning
confidence: 99%
“…After postoperative evaluation, it was concluded that, though the graft take-up rates in both of the groups were the same, the hearing improvements were found to be significantly better in the group where correction of foreshortening was done. No other study from the Indian author under mentioned criteria of search was found to have published on this topic [44].…”
Section: Techniques Of Surgerymentioning
confidence: 99%